Development of a game for history course of secondary school students - Ghulamani, Sumbul; Shah, Asadullah; Khowaja, Kamran (IEEE, 2017)
Computer Games have changed the world as they influence our culture and lives. Games with educational purposes are being incorporated in almost every field of life. These games help to learn the concepts in interesting and interactive ways. A lot of research is being conducted on Digital Game Based Learning, with purpose to study existing strategies and propose different models to improvised Learning. This paper presents the development of a game prototype for history based courses for the secondary school kids. The purpose of this prototype is to improvise learning of students in these courses.